KONFLIK ELLEN DEMPSEY MENGHADAPI OBSESI MASA LALU DALAM NOVEL LOVE THE ONE YOU’RE WITH KARYA EMILY GIFFIN. - Nadiana, Nabila Arlita (LANTERN (Journal on English Language, Culture and Literature), 2012)
Love the One You’re With is a novel written by Emily Giffin in 2008. The novel tells about the love of an obsessed woman over a man in the past. The purpose of this research is to identify Ellen Dempsey’s love and obsession as the main character of the novel. Library research is conducted in this study. The writer uses intrinsic and extrinsic theory. The analysis of intrinsic elementincludes character, setting, and conflict of the novel. Extrinsic theory includes Obsession and Sigmund Freud’s concept of id, ego, and superego. The result of the research shows that Ellen's obsession and conflicts has affected her behavior that makes her fell hesitated. This condition brings her to a conflicts that happen with herself and external conflicts with other people. Thus, it can be inferred that love is deciding to be truly committed in Love the One You’re With.